Behaviour and enclosure use of captive parma wallabies (Macropus parma): an assessment of compatibility within a mixed-species exhibit - Rendle, Jessica Amy Jane; Ward, Samantha; McCormick, Wanda Denise (Journal of Zoo and Aquarium Research, 2018)
The parma wallaby (Macropus parma) is considered to be a species of conservation concern. Collaborative breeding programs for this cryptic animal are in place in many zoos worldwide. Many zoos choose to house parma wallabies in mixed-species exhibits and a successful combination of species can greatly improve breeding prospects. However, there are potential health and welfare concerns and species compatibility requires consideration. This study investigates if a previously unreported housing of the parma wallaby and the Patagonian mara (Doliochotis patagonum), is congruous. Parma wallabies at Dudley Zoological Gardens were observed in two different housing systems; mixed-species (MS) and single species (SS) for nine days. Scan sampling of all individuals, across a range of behaviours previously reported for this species, was carried out at three 30 minute periods across the day. Differences in foraging behaviour were noted with parmas housed in the MS foraging significantly less than the SS group (p<0.01). A novel behaviour, agonistic directional urination, was also observed in the MS enclosure which was not observed within the SS group. Utilisation of the enclosure was analysed using a Spread of Participation Index (SPI); values revealed MS parmas utilised less of their enclosure, with a notable preference for areas not frequented by mara (W27=899.0, p<0.05). The MS parmas appeared to be affected by the presence of the mara, both behaviourally and in their enclosure use, this could be indicative of a negative welfare state. This study provides an indicator of species incompatibility, potentially affecting the welfare of captive parma wallabies and the future conservation of the species, and requires further investigation.